2004
DOI: 10.1210/jc.2003-032012
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Regulation of the Prokineticins (Endocrine Gland-Derived Vascular Endothelial Growth Factor and Bv8) and Their Receptors in the Human Endometrium across the Menstrual Cycle

Abstract: This study investigated the possible role of the newly discovered endocrine gland-derived vascular endothelial growth factors and their cognate receptors in the human endometrium during the menstrual cycle. Endocrine gland-derived vascular endothelial growth factors are also known as prokineticin (PK) 1 and PK2 and their receptors as PKR1 and PKR2. Expression of PK1 was elevated in the secretory compared with the proliferative phase of the menstrual cycle (P < 0.05). There was no temporal variation in expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
114
0
7

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(130 citation statements)
references
References 25 publications
9
114
0
7
Order By: Relevance
“…However, the pattern of receptor expression was distinct as endocrine cells expressed both PKR1 and PKR2 whereas capillary endothelial cells expressed only PKR1. In human endometrium, it has also been shown that the endothelial cells coexpressed both factors and both receptors, PKR1 being predominant (Battersby et al 2004). Several studies have reported that PKR1 and PKR2 present similar affinities for both factors and trigger the same signaling cascades in Figure 7 Effect of EG-VEGF/PK1 on ERK1/2 and Akt protein phosphorylation.…”
Section: Discussionmentioning
confidence: 94%
“…However, the pattern of receptor expression was distinct as endocrine cells expressed both PKR1 and PKR2 whereas capillary endothelial cells expressed only PKR1. In human endometrium, it has also been shown that the endothelial cells coexpressed both factors and both receptors, PKR1 being predominant (Battersby et al 2004). Several studies have reported that PKR1 and PKR2 present similar affinities for both factors and trigger the same signaling cascades in Figure 7 Effect of EG-VEGF/PK1 on ERK1/2 and Akt protein phosphorylation.…”
Section: Discussionmentioning
confidence: 94%
“…Prokineticins were originally identified as regulators of intestinal contraction but subsequently shown to affect vascular function, neuronal survival, nociception, immune responses, and gonadotropin releasing hormone systems (Battersby et al, 2004, Dorsch et al, 2005, LeCouter et al, 2003, Maldonado-Perez et al, 2007. Quickly after their discovery, the members of this family showed differential specificities of expression and preferential sites of actions.…”
Section: Prokineticins In Reproductionmentioning
confidence: 99%
“…While Bv8/PROK2 was associated to the neuronal system, EG-VEGF was more associated to the reproductive tract. EG-VEGF has been well studied in the ovary, uterus, testis, prostate and placenta (Battersby et al, 2004, Brouillet et al, 2010, Dorsch et al, 2005, Fraser et al, 2005,Hoffmann et al, 2007,2006, Hoffmann et al, 2009, LeCouter et al, 2001, LeCouter et al, 2003, Maldonado-Perez et al, 2007, Pasquali et al, 2006.…”
Section: Prokineticins In Reproductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reactions were performed using an ABI Prism 7900 (Applied Biosystems) using standard conditions. All primers and probes were previously validated, 20 and the sequences are listed in Table 2. All reactions were performed in triplicate.…”
Section: Quantitative Rt-pcr For Prokr In Fallopian Tube and The Oe-ementioning
confidence: 99%